2015
DOI: 10.1590/0100-5405/2078
|View full text |Cite
|
Sign up to set email alerts
|

Reação à Bipolaris maydis, agente causal da mancha foliar, em híbridos apomíticos de Panicum maximum

Abstract: A mancha foliar, causada por Bipolaris maydis, é a principal doença de Panicum maximum. A seleção de genótipos resistentes é a melhor estratégia para o controle desta doença. Com o objetivo de identificar fontes de resistência de P. maximum à mancha foliar, 92 híbridos apomíticos, originários de cruzamentos das cultivares Tanzânia-1 e Mombaça, e outros três genótipos sexuais foram testados. Em blocos casualizados, com oito Marcos, M.F.; Jank, L.; Fernandes, C.D.; Verzignassi, J.R.; Mallmann, G.; Queiróz, C.A.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…In seeds of P. maximum and Brachiaria spp., researchers have detected potentially pathogenic fungi such as the genera Curvularia, Fusarium, Phoma, Exserohilum, Cercospora and Helminthosporium, besides others, such as Alternaria, Aspergillus, Cladosporium, Epicoccum, Nigrospora, Penicillium and Trichoderma, (Marchi et al, 2010;Martinez et al, 2010;Mallmann et al, 2013;Marcos et al, 2015). These seeds can be a vehicle of dispersion of pathogens between regions (Vechiato et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In seeds of P. maximum and Brachiaria spp., researchers have detected potentially pathogenic fungi such as the genera Curvularia, Fusarium, Phoma, Exserohilum, Cercospora and Helminthosporium, besides others, such as Alternaria, Aspergillus, Cladosporium, Epicoccum, Nigrospora, Penicillium and Trichoderma, (Marchi et al, 2010;Martinez et al, 2010;Mallmann et al, 2013;Marcos et al, 2015). These seeds can be a vehicle of dispersion of pathogens between regions (Vechiato et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the accessions of P. notatum, it was observed that the PN 04 access was more susceptible than the PN 01 access, presenting a greater number of species of fungi. Some important and potentially pathogenic fungi have been detected in the seeds of Panincum maximum and Brachiaria spp., such as Curvularia, Phoma, Fusarium, Exserohilum, Cercospora, Fusarium, Cladosporium and Helminthosporium (Mallmann et al, 2013;Marcos et al, 2015;Silva at al., 2019). The species of phytopathogenic fungi most frequent in seed lots of Paspalum guenoarum ecotype "Azulão" were Bipolaris micropus, Curvularia geniculata, Fusarium incarnatum and Phoma herbarum (Gasparetto et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A mancha foliar é a principal doença que acomete a espécie Panicum maximum syn. Megathyrsus maximus, causada pelo fungo Bipolaris maydis (MARCOS et al, 2015).…”
Section: Principais Fungos Em Forrageirasunclassified